2020
DOI: 10.3390/en13092291
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making Process in the Circular Economy: A Case Study on University Food Waste-to-Energy Actions in Latin America

Abstract: Economies have begun to shift from linear to circular, adopting, among others, waste-to-energy approaches. Waste management is known to be a paramount challenge, and food waste (FW) in particular, has gained the interest of several actors due to its potential impacts and energy recovery opportunities. However, the selection of alternative valorization scenarios can pose several queries in certain contexts. This paper evaluates four FW valorization scenarios based on anaerobic digestion and composting, in compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…The outcomes demonstrated that the waste landfill scenario entails a greater global warming potential and freshwater Eutrophication impact than valorization scenarios. However, other impact divisions and costs are affected (Brenes-Peralta et al 2020). In the same vein, Keng et al performed a life cycle estimate advanced case study at the University of Nottingham Malaysia about composting food waste (Keng et al 2020).…”
Section: University Wastesmentioning
confidence: 99%
“…The outcomes demonstrated that the waste landfill scenario entails a greater global warming potential and freshwater Eutrophication impact than valorization scenarios. However, other impact divisions and costs are affected (Brenes-Peralta et al 2020). In the same vein, Keng et al performed a life cycle estimate advanced case study at the University of Nottingham Malaysia about composting food waste (Keng et al 2020).…”
Section: University Wastesmentioning
confidence: 99%
“…When the regulations are flexible, and adapted to the SMEs characteristics (thus supported and encouraged by government actions), competitive advantages and differentiation through environmental actions can be obtained [69]. Unfortunately, Latin American studies on environmental issues have focused mainly on waste generation, composition analysis, and decision-making approaches [70]. The latter is a pending topic for effectively assuming the country's environmental challenges.…”
Section: Waste Legislation: An Application Problemmentioning
confidence: 99%
“…In this sense, the universities' subcase suggests how monitoring and inference of causes in university populations can aid future decisionmaking and awareness-raising. FLW interventions are present in many studies from educational institutions [36,41,42] around the world. For instance, appreciations from the interviewees are supported by literature when considering the multidimensional reasons for their FLW: the size of servings, type of food that is wasted, and meal schedules play a significant role in the FLW behavior [42,43].…”
Section: Highlights From the Case Studymentioning
confidence: 99%